Analysis of Factors Affecting the Intention to Use Shopee Barokah (Case Study on Generation Z In Semarang City) - Najwa, Laila Fajri Khoirun; Kafabih, An'im (ASEAN Marketing Journal, 2025)
This study aims to determine the effect of attitude, subjective norm, perceived behavioral control, promotion and word of mouth on the intention to use Shopee Barokah. The population of this study is Generation Z Semarang City who knows Shopee Barokah but has never used it. Non-probability sampling technique, namely purposive sampling using primary data. Sampling was done by distributing questionnaires and obtaining 141 respondents. This research method uses binary logistic regression analysis with SPSS 26. The results showed that the variables of attitude, subjective norm, perceived behavioral control, promotion partially influenced the intention to use Shopee Barokah. Meanwhile, Word Of Mouth has no effect on the intention to use Shopee Barokah.